ANALISIS KENDALA-KENDALA POTENSIAL DALAM PENERAPAN TOTAL QUALITY SERVICE PADA HOTEL-HOTEL DI KOTA AMBON - Jupiter Dakael Dakael; Fransiska N. Ralahallo (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
The success of the competent hospitality is very dependent on how the hotelcan provide satisfaction to customers through the creation of quality services.Many companies have gained success because of applying the principles ofquality management. Total Quality Services (TQS) the principles of qualitymanagement services that can be used as strategic tools for the hospitality in orderto improve the quality of services. TQS application in order to obtain success,hospitality should be able to identify the constraints that exist.This study aimed to determine the potential constraints in theimplementation of TQS in hospitality. The study also examined potentialdifferences in the application of the constraints TQS between star hotels inAmbon. The instrument used in this study is a research instrument used inprevious research by Ngai and Cheng. Respondents are managers and supervisorswithin the scope of hospitality in Ambon.From the research results can be seen that out of the 17 indicators used inthis study there are four indicators expressed not as a potential obstacle to theapplication of TQS hotels in the city of Ambon. For an indicator to-1 that is aboutcultural change (variable labor and culture), the indicator for-5 on the knowledgeand understanding of the quality management system, the indicator for-7 ontraining and education quality, and indicators for-9 on the development of qualitymeasurement, The third indicator is part of the variable infrastructure factors.There are differences in potential constraints faced by each hotel in the city ofAmbon. In the first five-star hotel there are 15 potential obstacle is encountered,the 2-star hotel are 5 known obstacles, this 3-star hotel is only one obstacle courseand for the 4 and 5 star hotels do not have a potential obstacle to implementingTQS.